2014
DOI: 10.1038/ncomms4849
|View full text |Cite
|
Sign up to set email alerts
|

Specific adaptation of Ustilaginoidea virens in occupying host florets revealed by comparative and functional genomics

Abstract: Ustilaginoidea virens (Cooke) Takah is an ascomycetous fungus that causes rice false smut, a devastating emerging disease worldwide. Here we report a 39.4 Mb draft genome sequence of U. virens that encodes 8,426 predicted genes. The genome has B25% repetitive sequences that have been affected by repeat-induced point mutations. Evolutionarily, U. virens is close to the entomopathogenic Metarhizium spp., suggesting potential host jumping across kingdoms. U. virens possesses reduced gene inventories for polysacch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
222
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 197 publications
(229 citation statements)
references
References 62 publications
5
222
1
1
Order By: Relevance
“…reported that effectors cluster non-randomly in the genome of the bacterium Legionella pneumophila . Clustering of effectors has also been observed in the maize smut pathogen Ustilago maydis 56 and rice false smut pathogen Ustilaginoidea virens 57. Interestingly, plant R genes are also frequently found to occur in clusters58.…”
Section: Discussionmentioning
confidence: 89%
“…reported that effectors cluster non-randomly in the genome of the bacterium Legionella pneumophila . Clustering of effectors has also been observed in the maize smut pathogen Ustilago maydis 56 and rice false smut pathogen Ustilaginoidea virens 57. Interestingly, plant R genes are also frequently found to occur in clusters58.…”
Section: Discussionmentioning
confidence: 89%
“…RFSm is an example of such a disease. Our knowledge concerning the disease cycle and epidemiology of RFSm is minimal and incomplete or even contradictory (Lee and Gunnell, 1992;Zhang et al, 2014). While there have been "many hypotheses and much speculation" on the disease cycle of RFSm, there remains lack of experimental evidences to prove or disprove those hypotheses (Tang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…RNA sequencing (RNAseq) technology has become more frequently used to profile fungal pathogen gene expression at particular phases of plant infection (de Jonge et al, 2012;Kleemann et al, 2012;O'Connell et al, 2012;Soanes et al, 2012;Cantu et al, 2013;Garnica et al, 2013;Hacquard et al, 2013;Meinhardt et al, 2014;Zhang et al, 2014). However, comparatively few studies (Kawahara et al, 2012;Yang et al, 2013;Yazawa et al, 2013) have simultaneously analyzed the responses of both pathogen and host, and very few have undertaken such an analysis throughout a complete pathogen reproductive cycle.…”
mentioning
confidence: 99%